المستمر Matlabعن طريق الماتلاب HVDC دراسة ومحاكاة نظام نقل الطاقة بإستخدام الضغط العالي للتيار - محمد الجيلي جبارة احمد; محمد بابكر خضر بابكر; محمد يوسف العوض حمد (محمد بابكر خضر بابكر, 2018)
الهدف الرئيسي من هذا البحث هو تطبيق نظام نقل القدرة عن طريق الضغط العالي المستمر HVDC Transmission لربط شبكتي تيار متردد غير متزامنتين (لهما تردد مختلف) باستخدام برنامج Matlab Simulink للقيام بنمذجة النظام حاسوبياً. تبحث هذه الدراسة لتوضيح مدى أفضلية HVDC في الظروف المختلفة اقتصادياً وبيئياً ومن ثم معرفة أداء نظام HVDC في ظل ظروف التشغيل العادية Normal وظروف التشغيل غير العادية Abnormal. أظهرت هذه الدراسة كفاءة نظام نقل القدرة عن طريق الضغط العالي للتيار المستمر لنقل القدرة الكبيرة بفقودات قليلة جداً بين نظامين مختلفين التردد. Abstract The main objective from this research is application of power system Transmission by high voltage DC (HVDC) to link two network AC current Asynchronouses (it has Different Frequency).by use program of MATLAB Simulink to work the simulation system by computer This study searching the explanation the best rang of high voltage DC in varies state, Economically and Environmentally . and then Knowing The performance of high voltage DC in the normal operation circumstances and innormal operation circumstances . This study shown the Efficiency of power system transmission by means of high voltage DC to transmission large power by very little losses between two systemes has different frequency.